1990
DOI: 10.1002/jsfa.2740510407
|View full text |Cite
|
Sign up to set email alerts
|

Polyacetylenes in normal and waterstressed ‘Orlando Gold’ carrots (Daucus carota)

Abstract: The effect of water stress on the polyacetylenic constituents of carrots (Daucus carota L, cv 'Orlando Gold') was studied by liquid chromatographic analysis. Eleven polyacetylenes were isolated fiom plants grown in the greenhouse under normal conditions and under conditions simulating drought or waterlogging. Three compounds were ident$ed. These include the known carrot polyacetylenes falcarinol (cis-heptadeca-1,9-diene-4,6-diyn-3-01), falcarindiol (cis-heptadeca-l,9-diene-4,6-diyn-3,8-diol), and falcarindiol-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
40
2

Year Published

2006
2006
2018
2018

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 62 publications
(48 citation statements)
references
References 6 publications
6
40
2
Order By: Relevance
“…Polyacetylenes are well-known antifungal compounds that may accumulate during post harvest storage or during growth in the field, and hence may explain large differences between carrot cultivars/genotypes in their total content of polyacetylenes as well as of individual polyacetylenes [13]. Other factors that have a significant impact on the polyacetylene content are water stress, storage time, location, root size and genotype [13,31,34]. The mean CV calculated as a mean for three replicates of each genotype clearly showed that there was a large variation in the content of polyacetylenes between the investigated genotypes (Table 4).…”
Section: Spatial Distribution Of Polyacetylenes In Carrotsmentioning
confidence: 98%
See 2 more Smart Citations
“…Polyacetylenes are well-known antifungal compounds that may accumulate during post harvest storage or during growth in the field, and hence may explain large differences between carrot cultivars/genotypes in their total content of polyacetylenes as well as of individual polyacetylenes [13]. Other factors that have a significant impact on the polyacetylene content are water stress, storage time, location, root size and genotype [13,31,34]. The mean CV calculated as a mean for three replicates of each genotype clearly showed that there was a large variation in the content of polyacetylenes between the investigated genotypes (Table 4).…”
Section: Spatial Distribution Of Polyacetylenes In Carrotsmentioning
confidence: 98%
“…However, due to the low number of conjugated unsaturated bonds in their structures the excitation coefficients (e a6000 for two triple bonds in conjugation) of these compounds at their characteristic UV-maxima are generally very low and hence the sensitivity above 230 nm [25,31,33]. By detecting the compounds at 205 nm, the UV sensitivity is improved approximately ten times and consequently the detection and quantification limits of the polyacetylenes.…”
Section: Chromatographymentioning
confidence: 99%
See 1 more Smart Citation
“…In a greenhouse pot trial three novel polyacetylene compounds were found only in stressed carrots subjected to drought or waterlogged conditions. Levels of eight other polyacetylenes including falcarinol, falcarindiol and falcarindiol-3-acetate were lower in control samples, although an earlier field study by the same authors showed higher levels of polyacetylenes in field grown drought stressed carrots [95]. Both drought and salt stress cause production of ROS within the plant and result in increased levels of secondary metabolites, including phytochemicals.…”
Section: Biotic and Abiotic Stressmentioning
confidence: 78%
“…Moreover, abiotic factors, such as mechanical stress, is reported to increase the amounts of the key bitter tastants, members of the C17-polycetylenes, present in native carrots (Daucus carota L.) to efficiently high concentrations, causing a bitter off-flavor is perceived, occurring especially often during the production process for infant diet carrot products [79,80,[91][92][93][94][95][96][97][98]. In addition, a decrease in flavor quality accompanied by an increase in bitter taste has also been reported in raw hazelnuts (Corylus avellana L.) upon biotic stress challenges, such as upon infection by bugs, belonging to the hemipteran family, like Gonocerus acuteangulatus and Coreus marginatus [99].…”
Section: Sensomics -A Phenotyping Tool To Characterize Crops Flavor Imentioning
confidence: 99%